2004
DOI: 10.1016/j.jhsb.2004.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Function Following Late Neurolysis and Bypass Grafting for Upper Brachial Plexus Birth Injuries

Abstract: Eleven children ranging in age from 9 to 21 months underwent late nerve reconstruction for persistent shoulder paralysis following an upper brachial plexus birth injury. Only neurolysis was performed in three patients. Neurolysis and nerve grafting bypassing the neuroma with proximal and distal end-to-side repairs was performed in the other eight. All patients were followed for 2 or more years. Two patients underwent a secondary procedure before their final follow-up evaluation. All infants demonstrated signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 18 publications
0
49
0
3
Order By: Relevance
“…Surgical technique in this series included nerve grafting and nerve transfers to the suprascapular nerve, with good results reported in all children. 29 …”
Section: Microsurgical Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical technique in this series included nerve grafting and nerve transfers to the suprascapular nerve, with good results reported in all children. 29 …”
Section: Microsurgical Indicationsmentioning
confidence: 99%
“…It has been used to prevent contractures in the immediate postoperative period after microsurgery. 29,71,72 It has been used with serial casting as an adjunct to physical therapy. 73,74 The effect of the toxin is to reduce muscle tone and force to restore passive range of motion and joint alignment.…”
Section: Surgical Management Of the Shouldermentioning
confidence: 99%
See 1 more Smart Citation
“…40 All patients had biceps and deltoid recovery of M3 function or better. Over the last several years, Clarke and colleagues have suggested that early determination of the need for surgery in patients with NBPP likely selects some infants in whom recovery of function would occur without surgery.…”
Section: Discussionmentioning
confidence: 89%
“…Most authors would agree that surgery would be indicated for patients without hand to mouth function by 6-9 months of age, as patients without return of biceps function by this age would have poor outcomes without surgical intervention. 2,9,10,12,23 Paramount to our treatment protocol in this study was the use of intraoperative nerve conduction studies as a guide to determining whether to treat patients with neurolysis alone or with neuroma resection and interposition grafting. Historically, intraoperative nerve testing has been incorporated in the treatment algorithms and also reported in the surgical methods.…”
mentioning
confidence: 99%